Pengaruh Pengetahuan Perpajakan, Kesadaran Wajib Pajak dan Modernisasi Sistem Administrasi Perpajakan terhadap Kepatuhan Wajib Pajak Orang Pribadi - Yuliani, Ismi; Ratnasari, Fina (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This study addresses the persistent issue of Indonesia’s low tax ratio, which reflects limited taxpayer compliance and constrains the government’s ability to optimize public revenue. The research aims to analyze the influence of tax knowledge, taxpayer awareness, and the modernization of the tax administration system on individual taxpayer compliance. The study involved 325 undergraduate Accounting students at Pamulang University who are registered taxpayers, selected using an accidental sampling technique. Data were collected through a structured questionnaire and analyzed with multiple regression using SPSS 25. The results of the t-test indicate that tax knowledge (t = 4.010, p < 0.001), taxpayer awareness (t = 2.014, p = 0.045), and modernization of the tax administration system (t = 8.958, p < 0.001) all have significant positive effects on taxpayer compliance. The F-test (F = 76.833, p < 0.001) confirms that the three variables simultaneously influence compliance, with an adjusted R-squared of 0.413. These findings highlight the importance of strengthening tax education and promoting digital-based tax services to enhance voluntary compliance among young taxpayers, thereby contributing to sustainable tax revenue growth.